2020
DOI: 10.1093/mnras/staa665
|View full text |Cite
|
Sign up to set email alerts
|

Collision between molecular clouds – I. The effect of the cloud virial ratio in head-on collisions

Abstract: In a series of papers we investigate the effect of collisions between turbulent molecular clouds on their structure, evolution and star formation activity. In this paper we look into the role of the clouds' initial virial ratios. Three different scenarios were examined: both clouds initially bound, one cloud bound and one unbound, and both clouds initially unbound. Models in which one or both clouds are bound generate filamentary structures aligned along the collision axis and discernible in position-position … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…We found that that the different conditions caused star formation to occur at different times but that once star formation had begun, the subsequent evolution of the star formation rate was very similar in all of the simulations. Colliding clouds appear to form stars at a faster rate than clouds that do not collide, suggestive of some degree of triggering of star formation, but the difference in the star formation rates is around a factor of two to three, in line with the results reported by Tanvir & Dale (2020) but much smaller than the order of magnitude increase found by Wu et al (2017).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We found that that the different conditions caused star formation to occur at different times but that once star formation had begun, the subsequent evolution of the star formation rate was very similar in all of the simulations. Colliding clouds appear to form stars at a faster rate than clouds that do not collide, suggestive of some degree of triggering of star formation, but the difference in the star formation rates is around a factor of two to three, in line with the results reported by Tanvir & Dale (2020) but much smaller than the order of magnitude increase found by Wu et al (2017).…”
Section: Discussionsupporting
confidence: 82%
“…Despite the many simulations available, there is little agreement on how much the star formation rate is increased by a cloudcloud collision. Some authors find that the increase is around a factor of a few (Tanvir & Dale 2020) whilst others observe an order of magnitude increase (Wu et al 2017). These differences arise due to differences in the range of physical processes included in the simulation (e.g.…”
Section: Introductionmentioning
confidence: 98%
“…This means that the star formation resulting from slow gravitational collapse will be well-characterised in our simulations, but gas that is bumped into the high-density regime at shorter time-scales, as in shocks, may not be properly modelled. Simulations of discrete colliding clouds at high spatial resolution do indeed find an elevation of the star formation efficiency owing to the formation of filamentary structures and sheets on sub-cloud scales (Takahira et al 2014;Balfour et al 2015Balfour et al , 2017Wu et al 2017;Tanvir & Dale 2020). Similarly, previous simulations have investigated colliding flows driven by magnetohydrodynamic turbulence (e.g.…”
Section: Comparison To Simulations From the Literaturementioning
confidence: 59%
“…Recently, many hydrodynamic simulations of CCCs have been carried out (e.g., Takahira et al 2014;Balfour et al 2015;Takahira et al 2018;Shima et al 2018;Dobbs et al 2020;Tanvir & Dale 2020). Takahira et al (2014Takahira et al ( , 2018 and Shima et al (2018) simulated CCCs to study the dense core formation, assuming some initial turbulence in the clouds.…”
Section: Introductionmentioning
confidence: 99%